Jak3, STAT3, and STAT5 inhibit expression of miR-22, a novel tumor suppressor microRNA, in cutaneous T-Cell lymphoma - Sibbesen, Nina A.; Kopp, Katharina L.; Litvinov, Ivan V.; Jønson, Lars; Willerslev-Olsen, Andreas; Fredholm, Simon; Petersen, David L.; Nastasi, Claudia; Krejsgaard, Thorbjørn; Lindahl, Lise M.; Gniadecki, Robert; Mongan, Nigel P.; et al. (Impact Journals, 2015)
Aberrant activation of Janus kinase-3 (Jak3) and its key down-stream effectors, Signal Transducer and Activator of Transcription-3 (STAT3) and STAT5, is a key feature of malignant transformation in cutaneous T-cell lymphoma (CTCL). However, it remains only partially understood how Jak3/STAT activation promotes lymphomagenesis. Recently, non-coding microRNAs (miRNAs) have been implicated in the pathogenesis of this malignancy. Here, we show that (i) malignant T cells display a decreased expression of a tumor suppressor miRNA, miR-22, when compared to non-malignant T cells, (ii) STAT5 binds the promoter of the miR-22 host gene, and (iii) inhibition of Jak3, STAT3, and STAT5 triggers increased expression of pri-miR-22 and miR-22. Curcumin, a nutrient with anti-Jak3 activity and histone deacetylase inhibitors (HDACi) also trigger increased expression of pri-miR-22 and miR-22. Transfection of malignant T cells with recombinant miR-22 inhibits the expression of validated miR-22 targets including NCoA1, a transcriptional co-activator in others cancers, as well as HDAC6, MAX, MYCBP, PTEN, and CDK2, which have all been implicated in CTCL pathogenesis. In conclusion, we provide the first evidence that de-regulated Jak3/STAT3/STAT5 signalling in CTCL cells represses the expression of the gene encoding miR-22, a novel tumor suppressor miRNA.